2011
DOI: 10.4187/respcare.01002
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in COPD: A Systematic Review of the Prevalence, Quality of Life, and Mortality

Abstract: Anemia is common in patients with chronic diseases. However, little is known regarding the prevalence of comorbid anemia and its impact on quality of life, healthcare utilization, and mortality in patients with COPD. We conducted a systematic review and synthesis of the literature (1966 to March 2010). The prevalence of comorbid anemia in patients with COPD ranges from 7.5% to 34%, depending upon the populations selected and diagnostic tools employed to determine the level of hemoglobin. Comorbid anemia in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 52 publications
2
57
1
1
Order By: Relevance
“…Anemia is a common entity in COPD patients, and its prevalence varies from 7.5% to 34%, depending upon the selected populations and the diagnostic tools to determine the hemoglobin level 136. Several studies reported a connection between anemia and BMD.…”
Section: Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%
“…Anemia is a common entity in COPD patients, and its prevalence varies from 7.5% to 34%, depending upon the selected populations and the diagnostic tools to determine the hemoglobin level 136. Several studies reported a connection between anemia and BMD.…”
Section: Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%
“…A systematic review of the literature (1966–2010) estimates this prevalence to range from 7.5% to 34%, depending on the population selected and the diagnostic tools used 4. Further, lower haemoglobin levels were found to be independently associated with increased functional dyspnoea, reduced exercise capacity, impaired quality of life, premature mortality and greater likelihood of hospitalisations and healthcare resource utilisations 4. Raising haemoglobin through transfusion decreases minute ventilation and work of breathing in patients with COPD, with unloading of respiratory muscles, thereby improving the functional limitation 5…”
Section: Introductionmentioning
confidence: 99%
“…The causes of anaemia in COPD are probably multifactorial, such as nutritional disorders, occult blood loss, drug induced (theophylline, ACE inhibitors), carboxyhaemoglobin effect of cigarette smoking, and even oxygen therapy 4. A particular important cause in these patients may relate to anaemia of chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia has been associated with a higher mortality in elderly subjects, 21 in patients with heart failure, 22 and in those with aortic stenosis who underwent SAVR and TAVR. 3,4,15 Also, anemia has been associated with poorer functional outcomes in elderly subjects 21 and in patients with heart failure, 22 chronic kidney disease, 23 or COPD, 24 comorbidities that are, indeed, present in a high proportion of TAVR candidates. Accordingly, the presence of even mild anemia in this study was an independent predictor of poorer exercise capacity as evaluated by the 6MWT, of lower DASI and KCCQ scores, and of a trend toward a worse NYHA class in patients with severe aortic stenosis considered for TAVR.…”
mentioning
confidence: 99%